Mark scheme design for school- and college-based assessment in VTQs. (3rd July 2022) - Williamson, Joanna; Child, Simon
ABSTRACT: School- and college-based vocational and technical qualifications (VTQs) in England are required to award successful candidates a grade rather than simple pass or fail. Ensuring the reliability and validity of these grades is considered vital, particularly in light of the high-stakes purposes for which school assessment results in England are used. Whilst previous research has shown how mark scheme design can support examiner judgement, school- and college-based VTQs are assessed to a large extent by non-exam assessment, which is marked or graded by an assessor within the candidate's school or college. This article addresses the question of how mark scheme design can most effectively support reliable and valid assessment, by considering the distinctive characteristics of assessors' marking or grading task in this particular context. The article synthesises research on the nature of internal VTQ assessment, empirically validated studies in mark scheme design, and theoretical arguments, to produce a framework for mark scheme review. The framework constitutes a tool for evaluating design decisions, intended to help assessment designers in the process of mark scheme improvement, and hence to support school- and college-based VTQ assessment.